Malawi?s paprika producers needing help - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The General Manager of the Paprika Association of Malawi talks about the advantages and challenges of paprika growing and marketing for small scale farmers.